Experiential Learning through Sensory Integration in Improving Vocabulary Mastery of Children with Autism: A Single-Subject Study - Mirnawati, Mirnawati; Susanti, Dewi Juwita; Anjani, Lusiana Vera (Universitas Lambung Mangkurat, 2026)
Children with Autism Spectrum Disorder (ASD) often experience difficulties in language development, particularly in vocabulary acquisition, which is essential for communication and learning participation. This study aimed to examine the effect of experiential learning integrated with sensory integration on vocabulary mastery in a child with autism using a Single Subject Research (SSR) design. An A₁–B–A₂ design was employed across 22 sessions, consisting of baseline (4 sessions), intervention (11 sessions), and withdrawal phases (7 sessions). The intervention involved direct experiential activities supported by multisensory stimulation using 50 functional target words. Data were collected through a vocabulary performance test and analyzed using visual analysis, including trend, level, stability, and data overlap. The results showed an increasing trend in vocabulary performance during the intervention phase and relatively stable performance during the withdrawal phase. These findings suggest that experiential learning combined with sensory integration may support vocabulary development within the context of this single-subject study. However, the results are limited to the characteristics of the participant and research conditionsExperiential Learning through Sensory Integration in Improving Vocabulary Mastery of Children with Autism: A Single-Subject Study